The nitric oxide response in plant-associated endosymbiotic bacteria. (21st November 2011) - Cabrera, Juan J.; Sánchez, Cristina; Gates, Andrew J.; Bedmar, Eulogio J.; Mesa, Socorro; Richardson, David J.; Delgado, María J.
Abstract : Nitric oxide (NO) is a gaseous signalling molecule which becomes very toxic due to its ability to react with multiple cellular targets in biological systems. Bacterial cells protect against NO through the expression of enzymes that detoxify this molecule by oxidizing it to nitrate or reducing it to nitrous oxide or ammonia. These enzymes are haemoglobins, c -type nitric oxide reductase, flavorubredoxins and the cytochrome c respiratory nitrite reductase. Expression of the genes encoding these enzymes is controlled by NO-sensitive regulatory proteins. The production of NO in rhizobia–legume symbiosis has been demonstrated recently. In functioning nodules, NO acts as a potent inhibitor of nitrogenase enzymes. These observations have led to the question of how rhizobia overcome the toxicity of NO. Several studies on the NO response have been undertaken in two non-dentrifying rhizobial species, Sinorhizobium meliloti and Rhizobium etli, and in a denitrifying species, Bradyrhizobium japonicum . In the present mini-review, current knowledge of the NO response in those legume-associated endosymbiotic bacteria is summarized.